Auditory Phenotype and Histopathologic Findings of a Mutant Nlrp3 Expression Mouse Model - Kim, Yehree; Lee, Sang-Yeon; Kim, Min Young; Park, Kyusun; Han, Jin Hee; Kim, Jung Ho; Kim, Bong Jik; Choi, Byung Yoon (Frontiers in Neurology, 2022)
Objective: The pathogenesis of hearing loss in autoinflammatory disorders due to activation of the inflammasome remains incompletely understood. Previously no animals expressing mutant Nlrp3 survived to an age when hearing evaluation was possible due to embryonic lethality. We aimed to establish a novel mouse model that manifests quantifiable hearing loss with other syndromic features due to alteration of Nlrp3 and investigate the audiologic and histopathologic phenotype in the cochlea to clarify how the genetic alterations of NLRP3 could induce autoinflammatory hearing loss. Methods: To induce inner ear expression of the mutant Nlrp3, Nlrp3D301NneoR mice were bred with Gfi1Cre knock-in mice for conditional mutant Nlrp3 activation in the cochlea and hematopoietic cells. Hearing thresholds were measured. Hematoxylin-eosin sections of the cochlea, brain, kidney, and liver were examined under light microscopy. Immunohistochemical analyses of cochlear whole-mount preparations and frozen sections were performed. Results: We, for the first time in the literature, established a mouse model that manifests quantifiable hearing loss due to Nlrp3 alteration. ABR recordings of Nlrp3D301NneoR/+; Gfi1Cre/+ mice, albeit with limited life expectancy, exhibited severe to profound hearing loss at postnatal day 20 (P20). There was overall overexpression of mutant Nlrp3, and mutant Nlrp3 expression was noted in the spiral prominence, the outer sulcus region (Claudius cells and outer sulcus cells), the organ of Corti, the inner sulcus, and the spiral ganglion neurons in the cochlea. The hematoxylin-eosin sections of Nlrp3D301NneoR/+; Gfi1Cre/+ mice cochleae at P12 exhibited a disorganized organ of Corti between the outer hair cells/supporting Dieter’s cells and basilar membrane compared with the wild type mice, leading to a collapsed Nuel’s space. This morphologic feature gradually returned to normal by P15. Varying degrees of inflammation with lymphocytic infiltrations were observed in the brain, kidney, and liver. Conclusion: We report the first mutant Nlrp3 overexpression mouse model (Nlrp3D301NneoR/+; Gfi1Cre/+) that shows obvious overexpression of Nlrp3 in the cochlea, a transient developmental lag of the cochlea, and severe to profound hearing loss. We expect that this mouse line, which models human autoinflammatory hearing loss, could provide a valuable tool to elucidate the underlying pathogenic mechanism of inflammasome activation-mediated hearing loss.